Differential expression of tripartite motif-containing family in normal human dermal fibroblasts in response to porcine endogenous retrovirus infection - Kimsa, M W; Strzalka-Mrozik, B; Kimsa, M C; Mazurek, U; Kruszniewska-Rajs, C; Gola, J; Adamska, J; Twardoch, M (Folia biologica, 2014)
Antiretroviral restriction factors may play an essential role in the safety of xenotransplantation. Therefore, the present study focused on investigation of the changes in the tripartite motif-containing family (TRIM) gene expression in normal human dermal fibroblasts with and without lipopolysaccharide stimulation in response to porcine endogenous retrovirus infection. Analysis of the expression profile of TRIMs was performed using oligonucleotide microarrays and QRT-PCR. Nine (TRIM1, TRIM2, TRIM5, TRIM14, TRIM16, TRIM18, TRIM22, TRIM27 and TRIM31) statistically significantly differentially expressed genes were found (P < 0.05, one-way ANOVA). In conclusion, comprehensive analysis of retroviral restriction factor gene expression in human dermal fibroblasts before and after porcine endogenous retrovirus infection with and without LPS stimulation may suggest association of the selected TRIMs with antiretroviral activity.
Keywords: RNA, Messenger; zvířata; aminokyselinové motivy; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Amino Acid Motifs; fibroblasty; Gene Expression Profiling; Carrier Proteins; messenger RNA; Oligonucleotide Array Sequence Analysis; reprodukovatelnost výsledků; Sus scrofa; Animals; polymerázová řetězová reakce s reverzní transkripcí; Reverse Transcriptase Polymerase Chain Reaction; Reproducibility of Results; endogenní retroviry; Dermis; škára; stanovení celkové genové exprese; Endogenous Retroviruses; lidé; Humans; Fibroblasts; transportní proteiny